2008
DOI: 10.1007/s10811-008-9345-1
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of mycosporine-like amino acids isolated from three red macroalgae and one marine lichen

Abstract: Several standard in vitro assays were performed in order to determine the potential antioxidant capabilities of purified aqueous extracts of the mycosporine-like amino acids (MAAs), porphyra-334 plus shinorine (P-334 + SH), isolated from the red alga Porphyra rosengurttii, asterina-330 plus palythine (AS-330 + PNE), from the red alga Gelidium corneum, shinorine (SH), from the red alga Ahnfeltiopsis devoniensis, and mycosporine -glycine (MGly), isolated from the marine lichen Lichina pygmaea. The scavenging pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
170
0
10

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(190 citation statements)
references
References 44 publications
5
170
0
10
Order By: Relevance
“…However, the effect of nutrients was reflected by a preferential accumulation of some types of MAAs, but only in E. elongata collected from 2.0 m depth. The relative content of palythine in creased in nutrient-enriched algae, which has been associated with higher antioxidant activities compared to shinorine (de la Coba et al 2009). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the effect of nutrients was reflected by a preferential accumulation of some types of MAAs, but only in E. elongata collected from 2.0 m depth. The relative content of palythine in creased in nutrient-enriched algae, which has been associated with higher antioxidant activities compared to shinorine (de la Coba et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…reversible changes in photosynthetic efficiency and capacity, accumulation of ultraviolet screen compounds and increase of antioxidant activity . For instance, brown algae accumulate UV screen compounds (polyphenols) with a strong antioxidant activity under high photosynthetically active radiation (PAR) and UVR (Pavia et al 1997, Connan et al 2004, Cruces et al 2012, whereas the tolerance of most red algae to excessive light, including UV, is driven by the accumulation of mycosporine-like amino acids (MAAs) (de la Coba et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Al though no effect on total MAA content was found in E. elongata, a tendency to accumulate relatively more palythine under high CO 2 was ob served. It is known that palythine possesses a higher antioxidant capacity than the other MAAs (De la Coba et al 2009). Thus, even though this species may show a loss of carbonate skeleton under OA, it could still maintain high photoprotective and antioxidant capacities.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the well-recognized role of MAAs as natural sunscreens, some MAAs also demonstrate strong antioxidant capacity during photooxidative stress caused by ROS production. A number of in vitro studies indicated a role for MAAs as an antioxidant in scavenging ROS (30) and suppressing singlet oxygen-induced damage (22,73,97). Exposure to UVR has been shown to lead to DNA damage either directly or indirectly through ROS production, while UVR-induced DNA damage activates DNA repair enzymes or leads to apoptosis (10,12,42).…”
Section: Diverse Functions Of Maasmentioning
confidence: 99%